2009
DOI: 10.1093/europace/eup346
|View full text |Cite
|
Sign up to set email alerts
|

Trend of the main clinical characteristics and pacing modality in patients treated by pacemaker: data from the Italian Pacemaker Registry for the quinquennium 2003-07

Abstract: Italian PM Registry data for the study period reveal a stable pattern of PM utilization and indications. A higher use of dual-chamber pacing in comparison to single-chamber pacing was reported for all indications, despite inconclusive data of the major randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
4
18
1
Order By: Relevance
“…Our study demonstrated that patients with TPM therapy and PPMs had an advanced age and male predominance, consistent with worldwide PPM survey and recent studies for temporal trends of PPM 7–9 . Aging and male gender had higher comorbidities for cardiovascular events, 10,11 which might be responsible for advanced age and male predominance in patients requiring pacing.…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrated that patients with TPM therapy and PPMs had an advanced age and male predominance, consistent with worldwide PPM survey and recent studies for temporal trends of PPM 7–9 . Aging and male gender had higher comorbidities for cardiovascular events, 10,11 which might be responsible for advanced age and male predominance in patients requiring pacing.…”
Section: Discussionsupporting
confidence: 89%
“…This is reflected in the increasing use worldwide of DDDR pacing in SSS 21 22. To reflect contemporary practice more accurately, and to ensure that our results did not simply reflect increased incidence of syncope due to the development of AV block in our AAIR group, we performed repeat data analysis excluding the 54 patients from this group who required upgrade to DDDR pacing due to AV block.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Therefore, the percentage of pacemakers using DDD keeps rising worldwide, especially in developed countries. [2,3] …”
Section: Introductionmentioning
confidence: 99%